Control of Escherichia coli O157 on beef at 37, 22 and 4 °C by T5-, T1-, T4-and O1-like bacteriophages. (October 2015) - Liu, H.; Niu, Y.D.; Meng, R.; Wang, J.; Li, J.; Johnson, R.P.; McAllister, T.A.; Stanford, K.
Abstract: Efficacy of four bacteriophages (phages) and a cocktail for biocontrol of Escherichia coli O157 was assessed on beef samples stored at 4, 22 and 37 °C. Samples (3 × 3 × 1 cm) were contaminated with E. coli O157 (10 4  CFU/cm 2 ) and treated with single phages: T5-like (T5), T1-like (T1), T4-like (T4) and O1-like (O1), or a cocktail at two titers: multiplicity of infection (MOI) = 1000 and MOI = 10. In contrast to previous studies, use of virucidal solution prevented over-estimation of phage efficacy. Irrespective of temperature and MOIs, T5 was most ( P  < 0.001) and O1 least ( P  < 0.05) effective for biocontrol of E. coli O157, with relative efficacy of other phages temperature dependent. At 4 °C, T1 ( P  < 0.05) and cocktail ( P  < 0.001) were more effective than T4. In contrast, T4 was equally ( P  = 0.08, at 37 °C) or less effective ( P  = 0.003, at 22 °C) than T5. Phages were more effective ( P  < 0.001) against E. coli O157 at warmer temperatures and high MOI. As the beef supply chain includes hours of storage or transport at temperatures near 4 °C, this study demonstrates phages could significantly reduce E. coli O157 during this period. Highlights: T5-like phage was most effective for controlling E. coli O157 at 4 and 22 °C. Increasing multiplicity of infection increased efficacy of all phages except O1. Competitive interference among phages may have reduced cocktail efficacy. 144 h of phage treatment at 4 °C reduced E. coli O157 by 3.2 log 10  CFU/cm 2 . Phages show potential for controlling E. coli O157 in refrigerated meat.